2017
DOI: 10.1177/0263617417710141
|View full text |Cite
|
Sign up to set email alerts
|

Selective catalytic reduction of NO with NH3 on mixed alumina–iron (III) oxide pillared montmorillonite “Cheto” Arizona, modified with hexamminecobalt (III) chloride

Abstract: Montmorillonite intercalated with mixed alumina-iron (III) oxide pillars and promoted with hexamminecobalt (III) chloride was studied in selective catalytic reduction of NO with NH 3 . Pillaring process extended the interlayer spacing by 0.236 nm and increased specific surface area (SSA BET , without pillaring, showed no selective catalytic reduction activity, but still produced high amounts of N 2 O.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Moreover, the ion exchange properties of PCHs, which depend mainly on the clay minerals used for their synthesis, favor the introduction of catalytically active metal species in highly dispersed forms. These very promising properties of PCHs have sparked great interest in these materials as potential catalysts for various processes, including selective catalytic reduction of NO with ammonia (NH 3 -SCR) [13,15,30] and selective catalytic oxidation of ammonia (NH 3 -SCO) [67]. Chmielarz et al [72] reported promising results for the NH 3 -SCR process for PCHs obtained from synthetic saponite intercalated with silica pillars and modified with copper and iron via the ion exchange method.…”
Section: Porous Clay Heterostructures-pchsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the ion exchange properties of PCHs, which depend mainly on the clay minerals used for their synthesis, favor the introduction of catalytically active metal species in highly dispersed forms. These very promising properties of PCHs have sparked great interest in these materials as potential catalysts for various processes, including selective catalytic reduction of NO with ammonia (NH 3 -SCR) [13,15,30] and selective catalytic oxidation of ammonia (NH 3 -SCO) [67]. Chmielarz et al [72] reported promising results for the NH 3 -SCR process for PCHs obtained from synthetic saponite intercalated with silica pillars and modified with copper and iron via the ion exchange method.…”
Section: Porous Clay Heterostructures-pchsmentioning
confidence: 99%
“…The porous clay heterostructure (PCH) obtained through intercalation of synthetic saponite with silica pillars was used as the catalytic support for the preparation of the NH 3 -SCO catalysts [67]. Copper and iron were deposited into the PCH support via ion exchange method in the form of highly dispersed species, namely monomeric cations and small oligomeric metal oxide aggregates.…”
Section: Selective Catalytic Oxidation Of Ammonia (Nh 3 -Sco)mentioning
confidence: 99%
See 1 more Smart Citation
“…The special attention of many researchers has been recently directed to the application of modified activated carbon (AC) as NH 3 -SCR catalysts [22][23][24][25]. This is mainly due to its high specific surface area, well-developed system of pores, and hydrothermal durability [26,27]. The positive influence of activated carbon used as a catalyst support for the simultaneous removal of both NO x and SO 2 was confirmed by many researchers [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous systems have been proposed as catalyst carriers, e.g. activated carbons [8][9][10][11][12][13][14][15][16][17], aluminosilicates [18][19][20][21][22], zeolites [23][24][25][26], hydrotalcites [27][28][29], etc. Most often, delectron metals, such as Fe [20,22,[30][31][32][33], Cu [5,18,[34][35][36][37][38], Mn [8,[39][40][41][42][43], etc.…”
Section: Introductionmentioning
confidence: 99%